Petrography, Diagenesis and Paragenesis of Wadi Halfa Oolitic Ironstone Formation, North Sudan - Daoud, Abazar M. A.; Rashed, M. A.; Sediek, Kadry N.; Elamein, A. M.; Elsharief, A. M. (European Journal of Applied Sciences, 2021)
Utilizing petrography, diagenesis and paragenesis are the major step to study the sediments of Wadi Halfa Oolitic Ironstone Formation for their origin and economic potential. Petrographical analysis of Wadi Halfa Oolitic Ironstone Formation were carried out depending on the investigation of six vertical lithofacies profiles from the region of Wadi Halfa. The petrographic classification of sandstone samples of Wadi Halfa Oolitic Ironstone Formation according to mineral composition (quartz, lithic fragments, and feldspars) are classified as quartzarenite 66.7%, sub lithic arenite 20.9% and subarkose 12.5%. The provenance of the sandstone revealed that all sample were derived mainly from interior stable craton. The stable craton offered good environments for detrital constitution to be recycled and transported for relatively long-distance. The present study adopted an intergranular pressure solution (IGV) diagram for IGV values more than 50 percent for all studied samples indicating that more of their original porosity has been destroyed cementation rather than by compaction processes for most samples.